Leptin modulates noradrenaline release in the paraventricular nucleus and plasma oxytocin levels in female rats: A microdialysis study - Kutlu, Selim; Aydin, Mehmet; Alcin, Ergul; Ozcan, Mete; Bakos, Jan; Jezova, Daniela; Yilmaz, Bayram (Elsevier, 2010)
The neural control and mutual inter-relationships among individual factors involved in the regulation of food intake and simultaneously related to reproduction are far from being understood. We have suggested that at least some of the effects of orexigenic and anorexigenic peptides might be mediated via noradrenalin release in the paraventricular nucleus (PVN). The main hypothesis was that leptin has an inhibitory action on oxytocin secretion and hypothalamic release of noradrenalin. Non-pregnant female rats in their diestrus were subjected to cannulation of the carotid artery and a microdialysis procedure with the probes in the hypothalamic PVN. Intra-arterial administration of cholecystokinin-8 (CCK) at the dose of 50 mg/kg was used to induce oxytocin and noradrenalin release. Leptin (10 mg/5 ml) was intracerebroventricularly injected in addition to CCK. Blood and microdialysis samples were collected at 20-min intervals for 80 min. Central administration of leptin significantly reduced both plasma oxytocin and hypothalamic noradrenalin responses to CCK at 20 min following the treatments. in conclusion, leptin may inhibit oxytocin secretion by lowering noradrenergic neurotransmission in the PVN. The modulator effect of leptin on noradrenalin release in the PVN may be related to feeding behavior. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Leptin; Noradrenaline; Oxytocin; CCK; Brain microdialysis